ChemInform Abstract: Recent Advances in Cancer Treatment by Iron Chelators. Issue 9 (February 2016) - Corce, Vincent; Gouin, Sebastien G.; Renaud, Stephanie; Gaboriau, Francois; Deniaud, David
Abstract: Review: 60 refs.